Factors associated with adequate levels of knowledge about type 2 diabetes mellitus among outpatients of health service networks in Bogotá D.C., Colombia. - Vásquez, Skarlet Marcell; Villar, Juan Carlos; Torres-López, Luz Ángela; Barrera, Edgar Camilo; Balcázar-Muñoz, Ángela Manuela (Revista Facultad de Medicina de la Universidad Nacional de Colombia, 2024)
Introduction: One of the factors impacting the clinical outcomes of patients with type 2 diabetes mellitus (T2DM) is the level of knowledge about their condition. Little is known regarding knowledge of T2DM among Colombian patients and the factors associated with their level of knowledge. Objective: To identify the factors associated with having an adequate level of knowledge about T2DM in patients with this diagnosis treated in outpatient health services of Bogotá, D.C., Colombia. Materials and methods: Cross-sectional study conducted in 1068 adults with T2DM treated in 2021 in the outpatient services of 53 health care institutions of four health networks of Bogotá D.C. Consecutive patients were recruited at each institution for a telephone survey based on a randomly selected case. A questionnaire with 9 questions on T2DM was administered to the participants (6 questions were validated due to their relationship with the age of diagnosis [in years] or HbA1c levels). An adequate level of knowledge was understood as correctly answering 4 of the 6 validated questions. A multiple logistic regression analysis was performed to identify factors associated with having an adequate level of knowledge. Results: Participants' median age was 63.97 years, 64.98% were women, and the time elapsed since diagnosis was >10 years in 26.68%. Furthermore, 24.72% (95%CI: 22.23-27.39) showed an adequate level of knowledge. Being female (OR=1.63), having a level of schooling above elementary education (OR=1.82), having an occupation (OR=1.70), having a diagnosis of T2DM >5 years (OR=1.49), and having ≥1 comorbidity/history of major health condition (OR=1.48) were associated with an adequate level of knowledge about T2DM. Conclusion: One in four patients with T2DM in Bogotá showed an adequate knowledge of their condition. Given the amount and variety of patients with low levels of knowledge, it is essential to implement educational programs, particularly for men with a low level of education and recent diagnosis.